Thermal expansion of solid solutions Kr-CH4 at temperatures of liquid helium - Aleksandrovskii, A.N.; Gavrilko, V.G.; Dolbin, A.V.; Esel`son, V.B.; Manzhelii, V.G.; Udovidchenko, B.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A negative contribution of the CH4 impurity to the thermal expansion of the solution has been revealed in the dilatometric studies of solid Kr + 0.76% CH4, Kr + 5.25% CH4, and Kr + 10.5%CH4 solutions at 1-23 K. It is shown that the negative contribution results from changes in the occupancyof the ground state of the A-modifications of isolated CH4 molecules. Assuming that the CH4 impurity singles and clusters contribute to the thermal expansion independently, we can estimate their contributions. The contribution of the singles to the thermal expansion of the solid solution is negative. The energies of the first excitational rotational states were determined for singles and two-body and three-body clusters of the CH4 molecules.